Komunikasi Interpersonal dalam Meningkatkan Motivasi Belajar Mahasiswa - Chairunnisah Putri Ayu Ningsih; Emi Puspita Dewi (Wardah, 2022)
Abstract: The purpose of this study was to look at interpersonal communication that can affect the increase in learning motivation of students of the Faculty of Da'wah and Communication, State Islamic University of Raden Fatah Palembang. The research method uses quantitative research with a simple linear regression research design with a population of 2759 students with sampling using the slovin formula obtained 350 students. The research results show the equation Y = 43.361+0.341, thus interpersonal communication has a positive value of 43.361. then learning motivation will increase by 0.341 in learning activities. As well as the contribution of the interpersonal communication variable, namely 97%, to student learning motivation, thus it is very important for lecturers to build interpersonal relationships with students so that motivation in learning can run according to the goals of Higher Education. Keywords: Interpersonal Communication, Learning Motivation